Performance Enhancement of IRS-Assisted Communication Systems Under Rayleigh Fading Channels - Chawla, Ravneet; Bansal, Bajrang (International Conference on Signal Processing and Communication (Online), 2025)
Intelligent reflecting surface (IRS) is a key enabling technology that helps in modifying the propagation environment. In this paper, we investigate the performance of an optimized IRS based communication system in the presence of single eavesdropper considering Rayleigh fading. It is assumed that the channel state information (CSI) of the transmitter-to-IRS's and IRS-to-receiver's channels is perfectly known to the IRS. The simulation results demonstrate that proposed optimized IRS based communication system has a noticeable performance improvement as compared to the random IRS based communication system in terms of channel capacity and secrecy capacity. Furthermore, our results show secrecy performance improvement with increase in number of IRS reflecting elements.